Analysis of The Influence of KTA On the Level of Anarchies Related to The Age and Fanatism Level of Football Supporters in Indonesia - Rianti Setiadi; Franky Franky (AIBPM Publisher, 2019)
Football is a very popular sport in Indonesia. Every football club must have a supporter group. Usually supporters have a high level of fanaticism so they are willing to fight to defend the club they support. Unfortunately, it is not uncommon for anarchist acts of supporters to even bring the death. The anarchist level of football supporters needs to be reduced. In Indonesia, every football supporter club issue a KTA (Membership Card) but to watch a football match directly, the existence of a KTA is not a necessity. This needs to be considered in order to reduce the occurrence of anarchist acts. Besides the existence of KTA, it is necessary to look at the age of supporters who are allowed to watch football matches live and also the level of fanaticism that exists. If it is true that the existence of KTA, age and level of fanaticism affect anarchist levels, then Indonesian football parties need to make arrangements for the football audience directly based on these factors. This is the aim of this research. The data used are secondary data consisting of 1547 football supporters Persija, Persib, Persebaya and Arema. The data analysis method used is multiple regression analysis. The results obtained are the existence of KTA makes the level of anarchist lower, younger age has higher anarchist level, high level of fanaticism has higher anarchist level.